2003
DOI: 10.1038/sj.labinvest.3700003
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of tissue inhibitor of metalloproteinases (TIMP)-2 promotes matrix metalloproteinase (MMP)-2 activation and cell invasion in a human glioblastoma cell line

Abstract: Local invasiveness is a characteristic feature of glioblastoma that makes surgical resection nearly impossible and accounts in large part for its poor prognosis. To identify mechanisms underlying glioblastoma invasion and motility, we used Transwell invasion chambers to select for a more potently invasive subpopulation of U87MG human glioblastoma cells. The stable population of tumor cells (U87-C1) obtained through this in vitro selection process were three times more invasive than parental U87MG cells and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 18 publications
(18 reference statements)
4
40
0
2
Order By: Relevance
“…In fact, it has been shown that their expression is significantly increased in inflammation (Shamamian et al, 2001) and in tumour invasiveness and metastatisation (Turck et al, 1996) processes. Metalloproteinases are in turn regulated by inhibitory molecules (Goldman and Shalev, 2004); the balance between the two molecular families being critical for control of proteolysis (Lu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that their expression is significantly increased in inflammation (Shamamian et al, 2001) and in tumour invasiveness and metastatisation (Turck et al, 1996) processes. Metalloproteinases are in turn regulated by inhibitory molecules (Goldman and Shalev, 2004); the balance between the two molecular families being critical for control of proteolysis (Lu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Gelatin zymography was performed as described previously, with modifications (Lu et al, 2004). Samples were mixed with zymogram sample buffer and loaded onto 8% polyacrylamide gels containing 0.1% gelatin.…”
Section: Gelatin Zymographymentioning
confidence: 99%
“…But, at lower concentrations, TIMP-2 is also essential for the efficient activation of pro-MMP-2. Due to the dual nature of TIMP-2, a small shift in the balance between TIMP and MMP levels may greatly modulate the invasive phenotype in tumor cells (10).…”
Section: Introductionmentioning
confidence: 99%